From page to stage - Gibson, Thomasina; Covener, Alan (United Kingdom : Classroom Video, 2009)
This program demonstrates how to select an appropriate script for your group and then take it from page to stage, in an organised and stress-free manner. With tips on promoting your play, planning a rehearsal schedule and keeping calm on performance night, students will be able to use this program as a guide throughout their production process.
Executive producer, Lynn Ovens
Presenter : Alex Morgan
DVD format
Keywords: Playwriting; Drama -- Technique